Prehospital Cardiovascular Autoregulatory Disturbances Correlate With the Functional Neuroanatomy of Acute Spinal Cord Injury. Issue 6 (15th March 2023) - Clark, Jillian M.; Bednarz, Jana M.; Batchelor, Peter E.; Skeers, Peta; Freeman, Brian J.C.
Abstract : Study Design: Retrospective study. Objective: The importance of attenuating the cardiovascular autoregulatory disturbances accompanying acute spinal cord injury (SCI) has long been recognized. This report assembles SCI emergency service data and correlates cardiovascular parameters to preserved functional neuroanatomy. Summary of Background Data: The nascent nature of evidence-based reporting of prehospital cardiovascular autoregulatory disturbances in SCI indicates the need to assemble more information. Materials and Methods: SCI data for <24 hours were extracted from ambulance and hospital records. The mean arterial pressure (MAP) was calculated. The International Standard for Neurological Classification of SCI (ISNCSCI) evaluates the primary outcome of motor incomplete injury (grades C/D) at acute presentation. Logistic regression was adjusted for multiple confounders that were expected to influence the odds of grade C/D. Results: A cohort of 99 acute SCI cases was retained; mean (SD) age 40.7±20.5 years, 88 male, 84 tetraplegic, 65 grades A/B (motor complete injury), triage time 2±1.6 hours. The lowest recorded prehospital MAP [mean (SD): 77.9±19, range: 45–145 mm Hg] approached the nadir for adequate organ perfusion. Thirty-four (52%) grade A/B and 10 (30%) C/D cases had MAP readings <85 mm Hg. In data adjusted for age, injury level, and triage time a 5 mm Hg increase in the lowest MAP value was associated with a 34% increase in the odds of having motor incomplete injury at acute presentation (adjusted odds ratio=1.34; 95% CI: 1.11–1.61; P =0.002). Conclusion: An important observation with implications for timely and selective cardiovascular resuscitation during SCI prehospital care involves significant negative associations between the depth of systemic hypotension and preserved functional neuroanatomy. Regardless of the mechanism, our confounder-adjusted logistic regression model extends in-hospital evidence and provides a conceptual bedside-bench framework for future investigations.